Anthropometric and motor performance profile of elite futsal athletes - Ademar Avelar; Katiucia Meneguzzi dos Santos; Edilson Serpeloni Cyrino; Ferdinando Oliveira Carvalho; Raphael Mendes Ritti Dias; Leandro Ricardo Altimari; Luis Alberto Gobbo (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n1p76 The purpose of the present study was to identify the anthropometric and motor performance profi le of futsal (indoor soccer) athletes in the second and third-placed teams in the Parana state championships (Brazil). Anthropometric(body mass, stature and skinfolds thickness) and motor performance (modified abdominal test, shuttle run, race of 30 m and 40 s) measures were obtained from twenty-seven male athletes (24.7 ± 6.4 years; 73.6 ± 7.6 kg; 174.8 ± 6.6 cm). For data analysis, athletes were grouped according to game positions. ANOVA one-way was used for comparisons between different positions, followed by Scheffé's post hoc test, with p < 0.05. Signifi cant differences were detected in body mass (midfielder < goalkeeper, p < 0.01), stature (midfielder < forward and goalkeeper, p < 0.01) and lean body mass (midfi elder < goalkeeper, p < 0.01). No significant differences in motor performance were detected between the athletes studied. The results of this study show that futsal athletes playing in different positions exhibit similar anthropometric and motor performance, in the majority of variables.